PWE-351 Acromegaly and colonic polyps revisited: time to change the guidelines?. (22nd June 2015) - Corrigall, D; Ziolkowski, BA; Woodland, P; Hannon, M; ChinAleong, J; Jenkins, P; Fairclough, P; Drake, W; Preston, S
Abstract : Introduction: Previous studies, including an important study from our own unit published nearly 20 years ago, have highlighted an increased risk of adenomatous colonic polyps in patients with acromegaly. 1 Current clinical guidelines suggest intense colonoscopic surveillance from the age of 40 for these patients. 2 Advances in detection and improved treatment of acromegaly may have influenced the prevalence of colonic neoplasms in this group, and may necessitate revision of current surveillance guidelines. We aimed to re-evaluate polyp prevalence in a more recent cohort of patients with acromegaly undergoing colonoscopic surveillance at the Royal London Hospital. Method: We interrogated our database to identify patients with acromegaly undergoing surveillance colonscopy between 2010 and 2015. In these patients we reported detection of premalignant and malignant lesions. Results: We identified 89 patients (41 males, age range 36–82, median age 64) who had undergone colonoscopy. In this 2015 cohort we identified 16 patients (18%) with at least one adenomatous polyp. Of these polyps, 69% were tubular adenomas and 31% were tubulovillous adenomas. Polyps in only two patients displayed high-grade dysplasia, the remainder displayed low grade dysplasia. No cancers were found, compared to 6 (5%) of the 1996 cohort. Conclusion: In comparison to the 1996 cohort we show a significantly (p = 0.04) lower detection rate of premalignant polyps in our patient group. In fact adenoma detection rates are similar to those seen in healthy colonoscopic screening populations. The reasons for this are likely to be multifactorial, but may in part be accounted for by advances in the diagnosis, management and monitoring of acromegaly (and thereby lower levels of GH and IGF-1). Consideration may be given to revisiting surveillance guidelines in these patients, resulting in fewer, perhaps more targeted procedures. Disclosure of interest: None Declared. References: Jenkins PJ et al . Clin Endocrinol. 1997 Jenkins PJ, Fariclough PD. Gut . 2002